Incidence Of Anemia In Pregnant Women In A District Hospital In Paraguay, During The Year 2024 - Pérez Velilla, Msc. María Adela; Toffoletti, Dra. Paola; Marian Wannis, Dra. Leila; Garlisi, Dra. Daniela (Salud Integral y Comunitaria, 2026)
Introduction: Iron deficiency anemia is the most common during pregnancy, caused by a decrease in hemoglobin concentration, a decrease in hematimetric indices and producing maternal-fetal complications during pregnancy.  Objectives: Determine the incidence of anemia in pregnant women in a District hospital in Paraguay, during the year 2024. Methodology: observational, descriptive cross-sectional. Through the registration of data from a district hospital in Paraguay without any type of intervention in the course of these. The sample consisted of 185 pregnant women. Results and discussion: the majority age was 28 and 37 years (52%), mostly from the city of Limpio (67%) and with a secondary educational level (53%). The educational and economic level is related to the appearance, The number of births and nutritional deficiencies can contribute to anemia, affecting fetal development. In the study, 54% of the patients had mild anemia, and 42% had moderate anemia, with the number of prenatal controls being a key factor in preventing complications. The absence of treatment in the mother affects fetal development, increasing the risk of premature birth. and limit the production of hemoglobin and oxygen in the maternal body.Conclusion: It was possible to identify the sociodemographic and clinical variables of the pregnant patients such as age, marital status, origin, educational level, parity, gestational age and diagnosis method, the type of anemia was satisfactorily determined according to the trimester of pregnancy and was correlated with the number of prenatal checkups.